Adaptation of admittance analysis to extract interface traps of a-Si: H/c-Si heterojunctions - Menda, Ugur Deneb; Ozdemir, Orhan (ELSEVIER SCI LTD, 2015)
Complete admittance expressions, adapted from the equations previously presented for Metal/Oxide/Semiconductor (MOS) structure, were derived and modified admittance approach was successfully applied on a-Si:H/c-Si heterojunction to deduce surface state density (N-ss) by employing capacitancevoltage (C-V) and conductance-voltage (G/omega-V) measurements. Through the approach, N-ss was determined as 6 x 10(12) cm(-2) eV(-1) that was mutually checked by continuum model, used previously for evaluating N-ss in MOS structure. Furthermore, locating such an amount at the interface of a-Si:H and c-Si, experimentally measured C-V curve was reproduced through AFORS-HET simulation program. Presence of such a large amount of N-ss was originated due to native oxide layer, confirmed through spectroscopic elipsometry measurement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Adapted admittance analysis; a-Si:H/c-Si heterostructure; Surface state density; Engineering; Materials Science; Physics